Iron status and its association with the educational performance and the intelligence of school going adolescents in the district of Kandy. - Dissanayake, D (My University, 2005)
The first phase of the study assessed the distribution and the determinants of iron deficiency ,among 13 - 15 year old adolescents in the district of Kandy. The hemoglobin (Hb) and the serum ferreting (SF) levels were assessed to determine the iron status. The second phase of the study was carried out in a sample of students included in the phase one. The educational performance and the intelligence were compared between iron deficient and iron sufficient groups